Enhancing Programmability in NoC-Based Lightweight Manycore Processors with a Portable MPI Library - Uller, João Fellipe; Souto, João Vicente; Penna, Pedro Henrique; Castro, Márcio; Freitas, Henrique; Méhaut, Jean-François (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2020)
The performance and energy efﬁciency provided by lightweight manycores is undeniable. However, the lack of rich and portable support for these processors makes software development challenging. To address this problem, we propose a portable and lightweight MPI library (LWMPI) designed from scratch to cope with restrictions and intricacies of lightweight manycores. We integrated LWMPI into a distributed OS that targets these processors and evaluated it on the Kalray MPPA-256 processor. Results obtained with three applications from a representative benchmark suite unveiled that LWMPI achieves similar performance scalability in comparison with the low-level vendor-speciﬁc API narrowed for MPPA-256, while exposing a richer programming interface.